Bridging the gap between policy and practice: a qualitative analysis of providers' field experiences tinkering with directly observed therapy in patients with drug-resistant tuberculosis in Addis Ababa, Ethiopia. Issue 6 (16th June 2020) - Mussie, Kirubel Manyazewal; Gradmann, Christoph; Manyazewal, Tsegahun
Abstract : Objectives: Drug-resistant tuberculosis (DR-TB) is one of the major public health threats in low-income countries such as Ethiopia. It is intertwined with larger socioeconomic and political factors that complicate its management and control. Whether directly observed therapy (DOT) is serving its purpose—better patient adherence and treatment outcome—still remains a debatable issue. To contribute to this discussion, this study explored health workers' field experiences tinkering with DOT in patients with DR-TB in Addis Ababa, Ethiopia. Design: A qualitative study using in-depth interviews and focus group discussion. Setting: Ten public healthcare facilities: eight health centres at Addis Ababa Health Bureau level and two TB-specialised hospitals at the Federal Health Bureau level in Ethiopia. Participants: 18 healthcare providers working with DR-TB patients. Results: Three findings emerged from the analysis. First, the purpose of DOT is to ensure that patients go to healthcare facilities and swallow pills under the observation of a healthcare provider. Thus, its rigid application could lead to the emergence of more DR-TB. Second, DOT should be tinkered with and its practice improved by incorporating more counselling and health education, with more flexibility towards, and attentiveness of, patient context. Third, there exists a family-like patient-provider relationship, and providers do understand their patients and empathise with them to provide better healthcare services. Conclusion: If rigidly implemented, DOT could lead to more DR-TB—a problem DOT was invented to resolve. Front-line healthcare providers are sensitive to the tragic experiences of DR-TB patients and empathise with them. Thus, they do not strictly implement DOT and are willing to take any blame resulting from tinkering with it. It is high time to shape the practice of DOT for DR-TB patients, with meaningful contributions from front-line healthcare providers.